Acid Ceramidase Protects Against Hepatic Ischemia/Reperfusion Injury by Modulating Sphingolipid Metabolism and Reducing Inflammation and Oxidative Stress - Jiang, Yuan; He, Xingxuan; Simonaro, Calogera M.; Yi, Bin; Schuchman, Edward H. (Frontiers in Cell and Developmental Biology, 2021)
Ceramide is a bioactive signaling lipid involved in the pathogenesis of numerous diseases. It also plays an important role in ischemia reperfusion (IR) injury via activation of inflammatory/oxidative stress-stimulated signaling pathways, resulting in tissue damage. Acid ceramidase is a lipid hydrolase that modulates the levels of ceramide, and as such has a potential therapeutic role in many human diseases where ceramide has been implicated. Here we investigated the therapeutic potential of recombinant acid ceramidase in a murine model of hepatic IR injury. Serum ALT, AST, and LDH activities, as well as oxidative stress (MDA) and inflammatory (MCP-1) markers, were increased in mice subjected to IR compared to a sham group. In contrast, these elevations were significantly lower in an IR group pretreated with a single injection of acid ceramidase. Histological examination by two different assessment criteria also revealed that acid ceramidase pretreatment alleviated IR-induced hepatocyte damage, including reduced evidence of cell death and necrosis. In addition, elevated ceramide and sphingosine levels were observed in the IR group compared to sham, and were markedly reduced when pretreated with acid ceramidase. In contrast, the levels of the protective signaling lipid, sphingosine-1-phosphate (S1P), were reduced following IR and elevated in response to acid ceramidase pretreatment. These changes in sphingolipid levels could be correlated with changes in the activities of several sphingolipid-metabolizing enzymes. Overall, these results indicated that sphingolipid changes were an important pathologic component of hepatic IR injury, and that acid ceramidase administration ameliorated these lipid changes and other downstream pathologic changes.